2022
DOI: 10.1039/d2dt00597b
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the chemistry of 12-membered pyridine-containing tetraazamacrocycles: from synthesis to catalysis

Abstract: This article provides an overview (non-comprehensive) on recent developments regarding pyridine-containing 12-membered tetraazamacrocycles with pyclen or Py2N2 backbones and their metal complexes from 2017 to the present. Firstly, the synthesis...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 112 publications
(151 reference statements)
0
5
0
Order By: Relevance
“…The results were indicative of a diffusion-controlled process and quasi-reversible Cu­(II/I) redox behavior at 100 mV s –1 (Table ). These negative redox values were a result of the overall strong donor character of PyN 3 -type ligands as reflected by the high log β Cu(II) values often observed with the 12-membered tetra-aza macrocyclic ligand family. , A difference of 100 mV for the Cu­(II/I) redox couple was observed between the two ligands functionalized with EDG; the [Cu NMe 2 PyN 3 ] 2+ complex ( E 1/2 = −1088 mV) had the most negative half-cell potential, followed by [Cu OMe PyN 3 ] 2+ ( E 1/2 = −988 mV). Functionalization with EWGs showed Cu­(II) complexes with more positive E 1/2 values overall compared to the EDGs counterparts ( [Cu CF 3 PyN 3 ] 2+ , E 1/2 = −914 mV).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results were indicative of a diffusion-controlled process and quasi-reversible Cu­(II/I) redox behavior at 100 mV s –1 (Table ). These negative redox values were a result of the overall strong donor character of PyN 3 -type ligands as reflected by the high log β Cu(II) values often observed with the 12-membered tetra-aza macrocyclic ligand family. , A difference of 100 mV for the Cu­(II/I) redox couple was observed between the two ligands functionalized with EDG; the [Cu NMe 2 PyN 3 ] 2+ complex ( E 1/2 = −1088 mV) had the most negative half-cell potential, followed by [Cu OMe PyN 3 ] 2+ ( E 1/2 = −988 mV). Functionalization with EWGs showed Cu­(II) complexes with more positive E 1/2 values overall compared to the EDGs counterparts ( [Cu CF 3 PyN 3 ] 2+ , E 1/2 = −914 mV).…”
Section: Resultsmentioning
confidence: 99%
“…While modifications on the 4-position of the pyridine ring moderate log β Cu(II) compared to that of the unsubstituted parent PyN 3 , the net log β Cu(II) values of the Cu(II) complexes studied herein are still among the highest reported to date. 27,41 Importantly, the pyridine modifications modulate log β Cu(II) to a lesser extent than previously studied modifications on the N atoms in the secondary amines, which suggests that fine tuning the Cu(II) binding stability of the R PyN 3 family may be a key consideration in retaining SOD reactivity under biological conditions. 26,27 [Cu R PyN 3 Cl][ClO 4 ] Complexes Do Not Show Significant Differences in Single-Crystal XRD (SC-XRD) Models.…”
Section: Strong Donors On the Pyridine Ring Increase The Cu(ii) Metal...mentioning
confidence: 94%
See 1 more Smart Citation
“…The macrocyclic tetradentate ligand L1 (Chart ) bears a functionality similar to that found in TPMA and Me 6 tren. This ligand has been pursued for applications in catalysis with a variety of transition metals. Interestingly, however, the Cu/L1 coordination chemistry has been unexplored in the context of halogen atom transfer. In this work, it is revealed that the parent [Cu I (L1)] + complex is capable of forming highly active e ATRA catalysts in situ through radical activation then capture and that this level of reactivity is unprecedented in the area of Cu-catalyzed halogen atom transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently found that Zn(II) [47] and Fe(III) [48] complexes of Pyclen ligands [49] are suitable catalyst for the CO 2 cycloaddition to epoxides. Inspired by this, we have studied the catalytic activity in this reaction of simple ammonium ferrate salts, obtaining excellent yields and selectivities under quite mild conditions [50] .…”
Section: Introductionmentioning
confidence: 99%